6G context-aware wireless network - Junshuai SUN; Yun ZHAO; Yingying WANG; Na LI; Huimin ZHANG; Xin SUN; Min YAN; Quan ZHAO; Gang LI; Xuan LIU; Guangyi LIU (Dianxin kexue)
Convergence of ICDT is one of the important technical trends in the evolution of wireless mobile communication.How to realize the convergence of wireless network and AI technology is an important topic in the evolution of wireless network.Based on the concept of native AI, AI was applied for wireless resources optimization.6G context-aware wireless network architecture was proposed and AI was introduced into RRM to form an intelligent controller (AI-driven RRM), which completed the intelligent wireless resource management.Driven by big data and artificial intelligence, intelligent management of wireless resources was realized.In the deployment, the intelligent controller is deployed according to its functions and supports dynamic function scaling, so that it can be deployed independently of base station to minimize the cost of hardware.